An alcohol oxidase biosensor using PNR redox mediator at carbon film electrodes - Barsan, Madalina M. (2008)
A new amperometric biosensor for ethanol monitoring has been developed and optimised. The biosensor uses poly(neutral red) (PNR), as redox mediator, which is electropolymerised on carbon film electrodes and alcohol oxidase (AlcOx) from Hansenula polymorpha as recognition element, immobilised by cross-linking with glutaraldehyde (GA) in the presence of bovine serum albumin (BSA) as carrier protein. Optimisation of variables affecting the system was performed and, for chronoamperometric measurements, a potential of -0.300 V versus saturated calomel electrode was chosen in 0.1 M sodium phosphate buffer saline at pH 7.5. The optimised biosensor showed a good sensitivity of 171.8 ± 14.8 nA mM-1 and the corresponding detection limit (signal-to-noise-ratio = 3) of 29.7 ± 1.5 [mu]M. Stability studies showed a good preservation of the bioanalytical properties of the sensor, 57.6% of its initial sensitivity remaining after 3 weeks (the sensor was used two to three times per week). No significant interferences were found from compounds usually present in wine. The biosensor was used for the determination of ethanol in Portuguese red and white wines.